Metabolomics Analysis Reveals Drought Responses of Trifoliate Orange by Arbuscular Mycorrhizal Fungi With a Focus on Terpenoid Profile - Liang, Sheng-Min; Zhang, Fei; Zou, Ying-Ning; Kuča, Kamil; Wu, Qiang-Sheng (Frontiers in Plant Science, 2021)
Soil water deficit seriously affects crop production, and soil arbuscular mycorrhizal fungi (AMF) enhance drought tolerance in crops by unclear mechanisms. Our study aimed to analyze changes in non-targeted metabolomics in roots of trifoliate orange (Poncirus trifoliata) seedlings under well-watered and soil drought after inoculation with Rhizophagus intraradices, with a focus on terpenoid profile. Root mycorrhizal fungal colonization varied from 70% under soil drought to 85% under soil well-watered, and shoot and root biomass was increased by AMF inoculation, independent of soil water regimes. A total of 643 secondary metabolites in roots were examined, and 210 and 105 differential metabolites were regulated by mycorrhizal fungi under normal water and drought stress, along with 88 and 17 metabolites being up- and down-regulated under drought conditions, respectively. KEGG annotation analysis of differential metabolites showed thirty-eight and thirty-six metabolic pathways by mycorrhizal inoculation under normal water and drought stress conditions, respectively. Among them, 33 metabolic pathways for mycorrhization under drought stress included purine metabolism, pyrimidine metabolism, alanine, aspartate and glutamate metabolism, etc. We also identified 10 terpenoid substances, namely albiflorin, artemisinin, (-)-camphor, capsanthin, β-caryophyllene, limonin, phytol, roseoside, sweroside, and α-terpineol. AMF colonization triggered the decline of almost all differential terpenoids, except for β-caryophyllene, which was up-regulated by mycorrhizas under drought, suggesting potential increase in volatile organic compounds to initiate plant defense responses. This study provided an overview of AMF-induced metabolites and metabolic pathways in plants under drought, focusing on the terpenoid profile.